ChemInform Abstract: Selective Oxidation of Alcohols to Esters Using Heterogeneous Co3O4—N@C Catalysts under Mild Conditions. Issue 2 (14th January 2014) - Jagadeesh, Rajenahally V.; Junge, Henrik; Pohl, Marga‐Martina; Radnik, Joerg; Brueckner, Angelika; Beller, Matthias
Abstract Co3O4 supported on carbon‐nitrogen material represents an excellent catalyst for the selective oxidation of alcohols to esters using benign oxygen as the final oxidant.